Producción, impacto y colaboración en investigaciones peruanas en psiquiatría y salud mental - Valle, Ruben (2020)
Objective: to measure production, impact, and collaboration in Peruvian research on mental health as reported in Scopus, from 1992 until 2018. Materials and methods: this is a bibliometric review that analyzed publications featured in Scopus and dealing with psychiatry and mental health that had been produced by researchers affiliated to Peruvian institutions. Scientific production analysis reviewed the number of papers published per year, the impact analysis assessed the number of times these papers were referenced in Scopus, and the collaboration analysis assessed institutions and country networks participating in the aforementioned pieces of research. Results: research dealing with psychiatry and mental health showed an increasing trend for the number of published papers, as well as with respect to the times such papers were referenced and also considering inter-institutional collaboration during the 1992-2018 time period. Nonetheless, the number of published papers is low, since only 12 papers per year have been published. Research is carried out by few institutions in Lima, it only partially deals with psychiatry and mental health issues, and it shows moderate leadership from Peruvian institutions. Conclusion: a larger number of national institutions is required for participating in research dealing with psychiatry and mental health. A collaborative effort is needed.